2018
DOI: 10.1177/0275074018775125
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Performance Management in Italian Local Government: The Necessity of Outcome Measures and Citizen Participation

Abstract: The purpose of this article is to identify what internal and external factors increase the probability of local officials actually using performance data for decision making within Italian local government, responding to one of the basic questions of performance management theory. Based on a sample of local governments from the Apulia region, we used an ordinary least squares regression model to show that local officials are more likely to engage in performance data use when they rely on input, output, and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…We checked for multicollinearity between independent variables based on the correlation coefficients shown in Table 3 and the variance inflation factor (VIF) for each independent variable. While some of the correlation coefficients were high, at above 0.7, they were nonetheless below the tolerance threshold level of 0.8 (Rivenbark et al, 2019; Studenmund, 2014). All the VIFs were below the tolerance threshold level of 10 (Chatterjee & Hadi, 2006; O’Brien, 2007), with a mean value of 2.93, ruling out a severe degree of multicollinearity.…”
Section: Empirical Strategymentioning
confidence: 99%
“…We checked for multicollinearity between independent variables based on the correlation coefficients shown in Table 3 and the variance inflation factor (VIF) for each independent variable. While some of the correlation coefficients were high, at above 0.7, they were nonetheless below the tolerance threshold level of 0.8 (Rivenbark et al, 2019; Studenmund, 2014). All the VIFs were below the tolerance threshold level of 10 (Chatterjee & Hadi, 2006; O’Brien, 2007), with a mean value of 2.93, ruling out a severe degree of multicollinearity.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Therefore, scholars have recommended that local officials wanting to measure the performance of a given program begin by identifying the program's mission, which will set the stage for developing service delivery goals and quantifiable objectives. The purpose of this deliberate process is to increase the probability that local officials will report on outcomes of service delivery (Ammons, 2012(Ammons, , 2020, which in turn increases the likelihood of performance data use (Ammons & Rivenbark, 2008;Ammons & Roenigk, 2015;Dimitrijevska-Markoski & French, 2019;Kroll, 2015;Moynihan et al, 2020;Moynihan & Pandey, 2010;Rivenbark et al, 2019). Broadbent and Laughlin (2009) also recognized the importance of objectives in their conceptual model of performance management, including the necessity of stakeholder consensus on the specific objectives and targets a given program wants to achieve.…”
Section: Measurement System Maturitymentioning
confidence: 99%
“…The research cited above aligns with Sanger (2008), who concluded that top-down leadership is more effective for performance measurement promotion and bottom-up leadership is more effective for performance data use. Rivenbark et al (2016) even found evidence of performance management in local governments of jurisdictions with populations between 1000 and 4999, concluding that bottom-up leadership plays an even more important role for performance management in smaller local governments, given their lack of organizational capacity from central administrative functions such as the budget office. Another dimension of this type of leadership appears in the research of Jacobsen and Andersen (2015), who found that employee-perceived leadership has a stronger relationship to organizational performance than leader-intended leadership.…”
Section: Devolved Decision Authoritymentioning
confidence: 99%
See 1 more Smart Citation
“…Both books fall somewhat short in one area involving the introduction of performance information into the budget process. During the paradigm shift from performance measurement to performance management, researchers and practitioners have clearly shifted from collecting and reporting performance measures to using them for decision making and understanding service impact (Ammons and Rivenbark 2008;Kroll 2015;Moynihan and Pandey 2010;Rivenbark, Fasiello, and Adamo 2019). In this regard, I was hoping for more concrete examples of performance management within the context of performance budgeting.…”
mentioning
confidence: 99%